Different Forms of Use of Historical Heritage and Module-Credit System in Formation of International Peace in Students - Rahimov Ruslan Jo’raboy o’g’li; Rustamov Firdavsbek Davirbek o’g’li; Bahromov Shohruxbek Bahodir o’g’li (Scientific Trends, 2024)
The article provides recommendations on the use of various interactive methods in the lessons of the use of historical heritage in the promotion of interethnic harmony in the social sciences and humanities in secondary schools, as well as the preparation of students for the credit-module system.
Keywords: Technology of education, teaching technology, educational technology, credit-module teaching system, credit, module, interactive educational technology, Interactive method in education, pedagogical technology, data link, story, find yourself, t-table, method, exercise.